Social Media Communication : Concep.ts p.ractices Data - law; ethics ([Place of publication not identified] : Routledge, 2017)
in the second edition of Social Media Communication: Concep.ts, p.ractices, Data, Law and Ethics, Jeremy Harris Lip.schultz p.resents a wide-scale, interdiscip.linary analysis and guide to social media. Examining p.latforms such as Facebook, Instagram, Snap.chat, LinkedIn, YouTube and p.interest, this book exp.lores and analyzes journalism, broadcasting, p.ublic relations, advertising and marketing. Lip.schultz focuses on key concep.ts, best p.ractices, data analyses, law and ethics$1 (Ball p.romoting the critical thinking p.rofessionals and..s
Keywords: communication; media; sicial